Bettagram: Digitalization Of The Marketplace For Android Based Buying Betta Fish: Bettagram: Digitalisasi Marketplace Jual Beli Ikan Cupang Berbasis Android - Yulianto Prasetyo; Mohammad Suryawinata (Academia Open, 2021)
Betta fish is one type of ornamental fish that is easily cultivated in an environment with minimal oxygen conditions and has a variety of unique colors that make Betta fish have a high selling value so that many people do this fish business. In the modern era, a marketplace digitization is needed to accommodate betta fish businessmen in order to facilitate transactions with buyers so that an application called Bettagram is created. The Bettagram application is an application based on the Android operating system built to use the Java programming language. Supported by firebase database-based data storage to store all data entered into this application. In the initial process of making this application, the first stage that is passed is the design of use case diagrams and activity diagrams. Furthermore, designing the application display design and designing the database structure for data storage. After that begins the building stage using the help of the android studio application.